Denaturing Gradient Gel Electrophoresis of PCR-Amplified gki Genes: a New Technique for Tracking Streptococci - van Vliet, M. J. (American Society for Microbiology (ASM), 2009)
Viridans group streptococci (VGS) are a well-known cause of infections in immunocompromised patients, accounting for severe morbidity and mortality. Streptococcus mitis group species (Streptococcus mitis, Streptococcus pneumoniae, Streptococcus oralis) are among the VGS most often encountered in clinical practice. Identifying the portal of entry for S. mitis group strains is crucial for interventions preventing bacterial translocation. Unfortunately, tracking the source of S. mitis group strains is dependent on a combination of extremely laborious and time-consuming cultivation and molecular techniques (enterobacterial repetitive intergenic consensus-PCR [ERIC-PCR]). To simplify this procedure, a PCR analysis with newly designed primers targeting the household gene glucose kinase (gki) was used in combination with denaturing gradient gel electrophoresis (DGGE). This gki-PCR-DGGE technique proved to be specific for S. mitis group strains. Moreover, these strains could be detected in samples comprised of highly diverse microbiota, without prior cultivation. To study the feasibility of this new approach, a pilot study was performed. This confirmed that the source of S. mitis group bacteremia in pediatric patients with acute myeloid leukemia could be tracked back to the throat in five out of six episodes of bacteremia, despite the fact that throat samples are polymicrobial samples containing multiple S. mitis group strains. In contrast, using the classical combination of cultivation techniques and ERIC-PCR, we could detect these strains in only two out of six cases, showing the superiority of the newly developed technique. The new gki-PCR-DGGE technique can track the source of S. mitis group strains in polymicrobial samples without prior cultivation. Therefore, it is a valuable tool in future epidemiological studies.